The Short Redaction of Joannes Zonaras’ Ἐπιτομὴ Ἱστοριῶν in the Slavonic Manuscript Tradition - Totomanova, Anna-Maria (Studia Ceranea, 2024)
The paper will focus on the four known Slavic witnesses of the so-called short redaction of Zonaras’ Chronicle and will try to explore its provenance and development. The conclusions will be based on the comparison of the content of the codices the short redaction is preserved in, on the one hand, and on the other – on the text critical and linguistic similarities and differences the witnesses show. The relations between the short redaction and the full version of Ἐπιτομὴ Ἱστοριῶν will also be tackled upon.